A reconnaissance survey of the Kachia grazing reserve, Kaduna state, Nigeria - Leeuw, P.N. de; Magaji, S.O. (International Livestock Centre for Africa, 1978)
Presents results of a survey to reconnaitre the physiography and woody & herbaceous vegetation cover, determine forage production & estimate carrying capacity of the Kachia Grazing Reserve, Kaduna State, Nigeria, w. an appendix on types & relative abundance of perennial & annual grasses in the 8 habitats identified in the area.